Da possibilidade de sonhar como utopia: narrativas secundaristas a alargar amanhãs - Mella, Lisiane Ligia (2023)
This research, developed in the line of Educational Policies of the Postgraduate Program in Education at the University of Passo Fundo, aims to reflect on the construction of tomorrow as a utopian opening through the narrative of high school youth. To problematize this opportunity, the investigation is based on life stories and readings of the world woven by young people about contemporary society and education. Peripheral educational territories, rural and urban centers, are taken as an analytical basis in order to position different perspectives of tomorrow, understanding youth narratives in social, cultural and historical terms. As for the nature of the problem, the study is anchored in the hermeneutic-dialectic qualitative method, supported by the reflexivity of the meanings that young people constitute amid the tensions and contradictions that emerge from history recognized as living time. The approach to the problem is articulated by (auto)biographical research, situating the methodological device of Ateliê da Palavra, created and developed singularly in six schools in the north and northwest of the state of Rio Grande do Sul, from the three educational territories investigated, integrating 26 young people from the third year of high school. The study is developed from four moments: the first is woven by the approach of the historical past to constitute contemporary time, positioning its effects to current forms of subjectivation, situating perspectives of tomorrows that encapsulate the possibility of experience. The second moment highlights the idea of ​​education supported in this study, linked to the emancipatory perspective of transforming life and tomorrow, opposing mercantile authoritarianism and entrepreneurship in vogue in today's society. In the third moment, the methodological-investigative path adopted in the research is highlighted, elucidating the ethical, aesthetic and formative foundations of Ateliê da Palavra, as well as the presentation of the participating high school youth and their schools. The fourth moment of the research situates the narrative opening of youth, epistemologically crossed by Ernst Bloch's principle of hope, by the notion of subject anchored in Lacanian psychoanalysis and by education from a Freirean perspective, of unfinishedness and creation. As a result of this narrative opening path, the study unfolds into three developments, namely: youth elucidation about the impasses of growing up in today's world amidst insecurities, inequalities and competitions derived from the social bond, highlighting the anguish faced with the ways of suffer and live contemporaneously. From then on, young people unveil horizons through the ability to narrate themselves and open gaps in discourse, recognizing themselves as subjects in an authorial perspective. As a second narrative unfolding, young people talk about their readings of the world and society through the stories that constitute them, linked to living conditions, work, cultural, family and social references, in order to feed a certain ideal of dream and tomorrow. Furthermore, high school youth narrate their perceptions about the current way of life, highlighting segregation and competitive logics, as well as the precariousness of work and bonds of solidarity. Such narratives also problematize the impact of digital communication on social relations and the lack of participation of young people in public life. The last narrative development concerns the youth experience of education, elucidating the meanings attributed to school, mediated by the principles of a banking education associated with the neoliberal aspect and the repercussions of this understanding on the act of being a student and being a subject in becoming. It is concluded that, as an expansion of the role of school in the construction of tomorrow, young people see it as a legitimate place of encounter with others and otherness, enunciating possibilities for opening horizons, dreams and futures. Consequently, it is noted that, by enabling openness to difference, public spaces such as schools are capable of boosting imagination towards tomorrow, with education being, when crossed by emancipatory perspectives of life and the world, a possible path to expand the becoming of each subject, as well as the becoming of humanity. Given the ability of each subject to publicly open their word in singularity, it is possible to argue that this is where the construction of new tomorrows resides, that is, in the possibility of narrating oneself and the world, collectively expanding the not-yet which represents tomorrow.